(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2017)
The efficacy of Trichoderma suspension on the recovery of fusarium wilt infected eggplant was studied at Bangladesh Agricultural University Farm during July 2014 to April 2015. Suspension of Trichoderma asperellum CP (IPM 33) (5.8×107 CFU ml-1) was applied to rhizosphere soils of eggplants @ 0, 20 and 40 ml plant-1. Fusarium oxysporum f. sp. melongenae was inoculated to flowering and fruiting stages of healthy plants by soil drenching method 48 hrs before and after application of Trichoderma suspension. Observations were made on the severity and recovering of wilting. The eggplant variety BAU Begun 1 was found resistant to fusarium wilt while other two varieties BAU Begun 2 and Dohazari G showed susceptible reaction. Pre-inoculation application of Trichoderma @ 40 ml plant-1 significantly reduced the severity of the disease. The vulnerability to fusarium wilt was higher at flowering stage of eggplant. Thus, the experimental results have opened up a possibility of using Trichoderma suspension over conventional farming inputs for sustainable and organic production of eggplant. Int. J. Agril. Res. Innov. & Tech. 7 (1): 38-42, June, 2017